Some comments on national policy on older persons - Sujaya, C.P. (1999)
The first-ever policy documented on older persons framed by the ministry of social justice and empowerment does not pay adequate attention to gender issues. It has an urban bias. The section on health care does not mention women, and property rights for women are not discussed. It does not explain how the implementation of its suggestions are to be financed. - Reproduced
Keywords: Women - India; Old age - India; Ageing - India; Elderly - India; Elderly